Sistem Informasi Perpustakaan - Ilham, Muhammad; Marpaung, Noveri Lysbetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Library is a room containt collection books arranged in such way, so it is easy to be found and used if needed any time by readers. In its management, Library still uses manual services. To facilitate library management process, Library Information System is created using PHP. The research produce an Information System that can make easier in managing process of information access, library data, member registration, book searching, and book booking. Initially, the library was managed manually in hardcopy form. And now, by using this information system so all data in this library can be stored in database. All reports can be printed out when needed, either seen in Library Information System. To use this system, all library members must register and login first. Keywords : Library, Manual Managing Process, Information System, Database System, PHP.